2018
DOI: 10.1051/0004-6361/201833129
|View full text |Cite
|
Sign up to set email alerts
|

Shotglas

Abstract: The presence of extreme horizontal branch (EHB) and blue hook stars in some Galactic globular clusters (GGCs) constitutes one of the remaining mysteries of stellar evolution. While several evolutionary scenarios have been proposed to explain the characteristics of this peculiar population of evolved stars, their observational verification has been limited by the availability of spectroscopic data for a statistically significant sample of such objects in any single GGC. We recently launched the SHOTGLAS project… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
34
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 105 publications
(191 reference statements)
3
34
0
1
Order By: Relevance
“…There is a distinct gap between H-sdB stars and He-sdOB stars in ω Cen (see the right panel). As mentioned by Latour et al (2018) this gap is predicted by the normal EHB models and delayed He-flash models (Miller Bertolami et al 2008;Moehler et al 2011, Lei et al 2015, 2016. However, this distinct gap is not present in our sample (see the left panel), and it seems to be filled up by some sdB stars and sdOB stars in the same region.…”
Section: Discussionsupporting
confidence: 49%
See 4 more Smart Citations
“…There is a distinct gap between H-sdB stars and He-sdOB stars in ω Cen (see the right panel). As mentioned by Latour et al (2018) this gap is predicted by the normal EHB models and delayed He-flash models (Miller Bertolami et al 2008;Moehler et al 2011, Lei et al 2015, 2016. However, this distinct gap is not present in our sample (see the left panel), and it seems to be filled up by some sdB stars and sdOB stars in the same region.…”
Section: Discussionsupporting
confidence: 49%
“…The He-sdOB populations (corresponding to BHk stars) in ω Cen are less represented in field hot subdwarf stars (e.g., ≈ 5% in the galactic disk, and ≈ 23% in the galactic halo, while ≈ 52% in ω Cen; Geier et al 2017b). The results in Latour et al (2018) demonstrated that BHk stars in GCs could experience a different formation origin from field hot subdwarf stars. Similar results have been obtained by Heber (2016, see Fig 23 in their study) by comparing EHB stars in ω Cen and NGC 2808 with the field hot subdwarf stars from the ESO-SPY project.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations